Stressful life events predict delayed functional recovery following treatment for mania in bipolar disorder - Yan-Meier, Leslie (2011)
Identifying predictors of functional recovery in bipolar disorder is critical to treatment efforts to help patients re-establish premorbid levels of role adjustment following an acute manic episode. The current study examined the role of stressful life events as potential obstacles to recovery of functioning in various roles. 65 patients with bipolar I disorder participated in a longitudinal study of functional recovery following clinical recovery from a manic episode. Stressful life events were assessed as predictors of concurrent vs. delayed recovery of role functioning in 4 domains (friends, family, home duties, work/school). Despite clinical recovery, a subset of patients experienced delayed functional recovery in various role domains. Moreover, delayed functional recovery was significantly associated with presence of one or more stressors in the prior 3 months, even after controlling for mood symptoms. Presence of a stressor predicted longer time to functional recovery in life domains, up to 112 days in work/school. Interventions that provide monitoring, support, and problem-solving may be needed to help prevent or mitigate the effects of stress on functional recovery.